Human Umbilical Cord Mesenchymal Stem Cells Inhibit the Function of Allogeneic Activated Vγ9Vδ2 T Lymphocytes In Vitro. (14th April 2015) - Liu, Xiaohuan; Feng, Ting; Gong, Tianxiang; Shen, Chongyang; Zhu, Tingting; Wu, Qihong; Li, Qiang; Li, Hong
Abstract : Background . Human umbilical cord mesenchymal stem cells (UC-MSCs) can regulate the function of immune cells. However, whether and how UC-MSCs can modulate the function of V γ 9V δ 2 T cells has not been fully understood. Methods . The PBMCs or V γ 9V δ 2 T cells were activated and expanded with pamidronate (PAM) and interleukin-2 (IL-2) with or without the presence UC-MSCs. The effects of UC-MSCs on the proliferation, cytokine expression, and cytotoxicity of V γ 9V δ 2 T cells were determined by flow cytometry. The effects of UC-MSCs on Fas-L, TRAIL-expressing V γ 9V δ 2 T cells, and V γ 9V δ 2 T cell apoptosis were determined by flow cytometry. Results . UC-MSCs inhibited V γ 9V δ 2 T cell proliferation in a dose-dependent but cell-contact independent manner. Coculture with UC-MSCs reduced the frequency of IFN γ + but increased granzyme B+ V γ 9V δ 2 T cells. UC-MSCs inhibited the cytotoxicity of V γ 9V δ 2 T cells against influenza virus H1N1 infected A549 cells and also reduced the frequency of Fas-L+, TRAIL+ V γ 9V δ 2 T cells but failed to modulate the apoptosis of V γ 9V δ 2 T cells. Conclusions . These results indicated that UC-MSCs efficiently suppressed the proliferation and cytotoxicity of V γ 9V δ 2 T cells and modulated their cytokine production. Fas-L and TRAIL were involved in the regulation. Cell contact and apoptosis of V γ 9V δ 2 T cells were not necessary for the inhibition.